Students Conceptual Understanding Abilities Through Flipped Classroom Learning - Juwita (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The Flipped Classroom learning model has become an increasingly popular approach in the world of education, especially in response to changes in the needs and characteristics of today's students. This approach allows students to learn the material beforehand at home through various resources provided by the teacher, enabling classroom time to be used for discussing, deepening and applying the concepts already learned. This research aims to analyze in-depth how the implementation of the Flipped Classroom learning model can influence students' understanding of concepts in various subjects and disciplines. The method used in this research is qualitative research with a Literature Review approach. Data and information were collected through exploration of literature from various sources, including books and articles related to the Flipped Classroom and students' understanding of concepts. Analysis was conducted to evaluate the implementation of the Flipped Classroom in developing students' understanding of concepts and the factors influencing its success. The results of the research indicate that the implementation of the Flipped Classroom significantly contributes to developing students' understanding of concepts in various subjects. Factors such as technological readiness, designing learning content that meets students' needs, the interaction between students and teachers, and the support provided by parents play a crucial role in the success of the Flipped Classroom. These findings are expected to provide insights for educators in designing and implementing learning approaches that focus on students' deeper and sustainable understanding of concepts.